Principles of Corporate Finance - Brealey, Richard A (McGraw Hill, 2024)
The latest edition in the Principles of Corporate Finance dynasty, the 14th edition continues in its tradition of showing how theory applies to the very practical problems and decisions faced by financial managers. Looking at what financial managers do and why, the book aims to give readers a solid understanding of theory so that they know what questions to ask when times change and new problems need to be analyzed, eventually standing as a reference and a guide to help them make financial decisions, not just study them.